PENGARUH SISTEM PEREKRUTAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN DI UNIT ADMINISTRASI RUMAH SAKIT AWAL BROS PANAM PEKANBARU - Wulandari, Atika; Suryandartiwi, Wiwik; Yuliana, Anastasya Shinta (Journal of Hospital Administration and Management (JHAM), 2022)
The hospital is one of the institutions that provide health services, this health service itself cannot be separated from the hospital administration. The administration section is a supporter in terms of decision making, activities in the administration of a hospital have a huge influence on the success or failure of a hospital. The influence of the human resource recruitment system in the Administration Unit greatly affects employee performance. The better the recruited employees, the better the performance provided. To get quality human resources, a good recruitment system is needed in order to produce quality resources as well. This study aims to determine the effect of the existing human resource recruitment system in the initial hospital bros panam. This type of research is qualitative with an analytical descriptive approach. There were 6 informants in this study and this study used the Rapid Assessment Procedures (RAP) model. This research was conducted on September 29 – October 18, 2022 at Awal Bros Panam Hospital. The results of the study found that there was still a lack of human resources in the administrative unit of the early bros panam hospital, there was no special SIMRS training in the administrative unit, besides that compensation also affected the performance of employees. And in recruiting new hospital employees it is in accordance with the SOP that has been set. It is recommended to add employees in the administrative unit, provide special SIMRS training in the administrative unit for employees who graduate from hospital administration and provide a special room for recruitment and provide written tests so that test results can be obtained quickly.